Implementasi Implementasi Konseling Individual Dengan Pendekatan Client Centered Dalam Membentuk Kemandirian Anak Berkebutuhan Khusus Di Slb-B Negeri Pembina Palembang - Rista Yuni Aprilina; Amin Sihabuddin; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
Independent is standing alone on the capital of confidence in oneself. From this basic capital, a person will have great confidence to be able to do and do something on his own. This research is entitled "Implementation of Individual Counseling with a Client Centered Approach in Forming the Independence of Children with Special Needs at SLB-B Negeri Pembina Palembang'. The purpose of this study is first to find out the description of the independence of children with special needs, secondly to find out the application of individual counseling with a client centered approach in forming the independence of children with special needs in SLB-B, the fostering country of Palembang. This type of research is qualitative research, using the filed research method, data collection techniques in this study are observation, interviews, and documentation. This study used data analysis and data reduction, where data reduction was carried out by summarizing the data obtained from interviews, observations, and data analysis. The results of this study are first, a description of the independence of children with special needs, namely freedom, initiative, self-confidence, responsibility, self-assertiveness, decision-making and self-control. The second is the application of individual counseling, where in the process of applying individual counseling with a client centered approach it can form the independence of mild mentally retarded children where mentally retarded children are slowly getting used to independent learning such as caring for themselves.